Use of Thoracic Ultrasonography to Improve Disease Detection in Experimental BRD Infection - Porter, Madison M.; McDonald, Paiton O.; Slate, Jamison R.; Kreuder, Amanda J.; McGill, Jodi L. (Frontiers in Veterinary Science, 2021)
Bovine respiratory disease (BRD) is caused by complex interactions between viral and bacterial pathogens, host immune status, and environmental stressors. In both clinical and research settings, current methods for detecting BRD in calves commonly focus on visual indicators such as attitude, nasal discharge and cough in addition to vital signs such as rectal temperature and respiration rate. Recently, thoracic ultrasonography (TUS) has become more commonly used in clinical settings in addition to physical examination to diagnose BRD. To assess the value of performing TUS during experimental BRD infection, thirty-two calves were challenged with bovine respiratory syncytial virus (BRSV), to mimic a viral infection, and thirty calves were infected with Mannheimia haemolytica, to mimic a bacterial infection. TUS was performed at regular intervals using a standardized method and scoring system in addition to daily clinical scoring. Although overall correlations between clinical scores and TUS scores were generally weak (maximum R2=0.3212), TUS identified calves with abnormal lung pathology that would have otherwise been misclassified based on clinical scoring alone, both on arrival and throughout the studies,. In addition, TUS had an increased correlation with gross lung pathology on necropsy (maximum R2=0.5903), as compared to clinical scoring (maximum R2=0.3352). Our results suggest that TUS can provide additional information on calf health at enrollment and throughout a study and may provide an alternative to terminal studies, due to the high correlation with lung pathology at necropsy.